An Explanatory Model of Vascular Access Care Quality: Results of a Cross-Sectional Observational Study - Sonia Casanova-Vivas; María Luisa Ballestar-Tarín; Pablo García-Molina; Ana Belén Lorente-Pomar; Ana Palau Gomar; Enrique Bdo. Hevilla Cucarella; José-María Blasco; Sonia Gomis-Baldoví (MDPI AG, 2024)
The management of nursing care regarding patients' vascular access is a priority. This study determines the contribution of the variables involved in the quality of care and maintenance of vascular access (VA) devices in admitted patients in the Valencian Community. Methods: Using the STROBE statement, an observational, cross-sectional study was conducted on 1576 VA devices. Data were collected using the INCATIV Questionnaire. We performed a multivariate analysis of the questionnaire variables. Results: In total, 50% had a good or very good assessment of the VA condition. This was positively correlated with anatomical location, dressing type, dressing date record, use of needle-free connectors (NFCs), date of last dressing change, presence of phlebitis, visibility of the insertion site and characteristics of the dressing's condition (p < 0.001). The model indicated that the presence of phlebitis was the clearest predictor of a poor VA care assessment (OR = 20.579), followed by no visibility of the insertion site (OR = 14.209). Results also indicated that uncovered VA lumens or no NFCs used were related to a negative quality assessment. Conclusion: By managing and controlling these variables, the likelihood of providing optimal care is ensured. This enables the establishment of a standardised care approach for all nursing professionals and the building of a new quality indicator.